Peningkatan Kualitas Jasa Fasilitas Kesehatan dengan Integrasi Metode IPA dan KANO - Shanty Kusuma Dewi; Ananda Rizky Calfintry Putri; Bagus Arif Dwi Winarko (Jurnal Sistem dan Manajemen Industri, 2018)
Health services facilities development and people mindset about health  make people more  critical in making decision to their needs of health services. The increased of the health fasilities made the owner to provide the best service, so they can be able to compete and growth. The purpose of this study is to improve the service quality of health service facility. The objective of this research is to improve the level of services quality on the health service. Integration of the IPA method and the Kano are used to determine which attributes should be improve to meet customer satisfaction. The result from this method are 14 attributes on the position keep up the good work  and 13 attributes must be improved.